EFFECTIVENESS OF REFLEXOLOGY MASSAGE IN REDUCING PROCEDURAL PAIN IN CHILDREN: A SYSTEMATIC REVIEW - Siti Zulva; Regidor III Dioso (rifascholarpublisher.com, 2026)
Background: Procedural pain is a frequent and clinically important issue in pediatric healthcare, commonly resulting from invasive or semi-invasive medical procedures. Inadequately managed pain can lead to immediate physiological stress as well as long-term psychological and behavioral consequences. Therefore, safe and effective non-pharmacological interventions are needed. Reflexology has been proposed as a complementary approach to reduce procedural pain in children. Objective: This systematic review aimed to evaluate the effectiveness of reflexology in reducing procedural pain among pediatric patients. Methods: A systematic review was conducted in accordance with the PRISMA 2020 guidelines. Literature searches were performed in PubMed, Scopus, ScienceDirect, and Google Scholar for studies published within the last five years. Studies were selected using the PICOS framework and included experimental designs involving children undergoing medical procedures and receiving reflexology interventions. Pain outcomes were assessed using validated instruments, including the FLACC Scale and Wong–Baker FACES Pain Rating Scale. Due to clinical and methodological heterogeneity, a narrative synthesis was conducted without meta-analysis. Results: Five studies met the inclusion criteria, including randomized controlled trials and quasi-experimental studies conducted in Egypt, India, and Turkey. The findings consistently showed that foot reflexology significantly reduced procedural or postoperative pain and anxiety compared with standard care or alternative interventions. Additional benefits included improved physiological stability, reduced fear, and enhanced postoperative comfort. Conclusion: Reflexology appears to be an effective, safe, and low-cost non-pharmacological intervention for reducing procedural pain in children.